2014
DOI: 10.1177/0013916514551604
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vivid Messages on Reducing Energy Consumption Related to Hot Water Use

Abstract: Research suggests that vivid and personalized interventions influence proenvironmental attitudes and behaviors. Through the use of immersive virtual environment technology, people can experience vivid environmental scenarios that are personalized to the individual. An experiment was conducted to investigate the impact of vivid and/or personal messages on energy savings behavior related to hot water use. Participants experienced a virtual shower in which they received feedback (varying in vividness and/or perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 54 publications
0
49
0
Order By: Relevance
“…It is important to note, therefore, emerging evidence that virtual reality-based interventions can translate into long-lasting behavioral change in the real world (Ahn, Bailenson, & Park, 2014; Bailey et al, 2015). Accordingly, one might consider attempts to simulate certain risk-taking environments in order to give teens virtual “experiences,” especially negative experiences, with risk taking in a safe, controlled environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, therefore, emerging evidence that virtual reality-based interventions can translate into long-lasting behavioral change in the real world (Ahn, Bailenson, & Park, 2014; Bailey et al, 2015). Accordingly, one might consider attempts to simulate certain risk-taking environments in order to give teens virtual “experiences,” especially negative experiences, with risk taking in a safe, controlled environment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that interacting with one’s weight-reduced self in a virtual environment could lead to better regulation of dietary practices (Kuo, Lee, & Chiou, 2016). Participants who were exposed to vivid messages about the amount of energy used for heat when experiencing a virtual shower used cooler water than those exposed to vague messages (Bailey et al, 2015). Given that vivid and concrete mental representations of events may induce closer psychological proximity (Liberman & Trope, 2008; Trope & Liberman, 2010), the question of whether the application of virtual reality technology to simulations of concrete future consequences of climate change would enhance risk perception is worthy of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This is because theoretically, in principle, it is possible to create Immersive Virtual Environments (IVEs) in which to “fully simulate what it is like to go into a non-immersive system” (Slater, 2009 , p. 3350). Moreover, a commonly held belief is that IVEs offer multisensory experiences, free navigation, and interactive possibilities in three-dimensional and digitally-rendered worlds from a first-person perspective, as if we were in the physical reality, but without being exactly in the physical reality (Bailey et al, 2014 , p. 573; Ahn et al, 2016 , p. 2; Oh et al, 2016 , p. 400; Herrera et al, 2018 , p. 4). This contraposition between the virtual world and the physical or non-virtual world is a core characteristic of immersion.…”
Section: Virtual Reality Technologies: Devices and Fundamental Aspectmentioning
confidence: 99%